Cost-effectiveness analysis of tissue plasminogen activator in acute ischemic stroke in Iran. (4th March 2018) - Amiri, Asrin; Goudarzi, Reza; Amiresmaili, Mohammadreza; Iranmanesh, Farhad
Abstract: Aims: Tissue plasminogen activator (tPA) is used to treat acute ischemic stroke up to 4.5 h after symptom onset. Its cost-effectiveness in developing countries is not specified yet. This study aimed to study cost-effectiveness of tPA in Iran. Methods: This is a cost-effectiveness analysis from the perspective of the third party payer to compare IV tPA with no tPA of ischemic stroke. A Markov model with a lifetime horizon was used to analyze the costs and outcomes. Cost data were extracted from the 94 patients admitted in two hospitals in Iran. All costs were calculated based on US dollars in 2016. Quality-adjusted life years (QALY) were extracted from previously published literature. Cost-effectiveness was determined by calculating ICER by TreeAge Pro 2011 software. Results: Lifetime costs of no tPA strategy were higher than tPA ($10, 718 in the no tPA group compared with $8, 796 in the tPA group). The tPA arm gained 0.20 QALY compared with no tPA. ICER was $8, 471 per QALY. ICER value suggests that tPA is cost-effective compared with no tPA. Limitations: The limitations of the present study are the reliance on calculated QALY value of other countries and difficulty in accessing patients treated with tPA. Conclusions: The balance of hospitalization and rehabilitation costs and QALYs support the conclusion that treatment with intravenous tPA in the 4.5-h time window is cost-effective from the perspectives of the third party payer and inclusion of tPA in the insurance benefit package being reasonable.